Efektivitas Media Audio Visual Terhadap Kemampuan Pemahaman Konsep IPAS Siswa Kelas IV SD Negeri 1 Selanegara - Pratama, Ilham Ananda; Riyadi, M. Ilham Rahmani; Isnawati, Febri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The learning of IPAS (Natural and Social Sciences) tends to present abstract concepts that are difficult for elementary school students, especially in the fourth grade, to understand. Old and conventional learning media that are verbal tend to be less effective in enhancing students' conceptual understanding. Therefore, there is a need for more interesting, interactive, and effective learning media, one of which is the use of audio-visual media. This research aims to determine whether the use of audio-visual media is effective in improving the conceptual understanding of IPAS among fourth-grade students at Selanegara State Elementary School 1. This research uses a quantitative approach with a one-group pretest-posttest design. The instrument used was a test to measure the understanding of IPAS concepts before and after the treatment. The sample in this study consisted of fourth-grade students from SD Negeri 1 Selanegara. The data analysis technique used was the t-test. The results showed an increase in the average score from 69 in the pretest to 87 in the posttest. The t-test indicated that this increase was statistically significant with a significance value of <0.001. Additionally, the students showed higher enthusiasm and paid more attention during the learning when audio-visual media was used.